Efficient IPv4-IPv6 translation mechanism for IMS using SIP proxy. Issue 1 (7th April 2022) - Khudher, Ali A.; Munther, Alhamza; Praptodiyono, Supriyanto
Next-generation IP Multimedia Subsystem (IMS) has a promise future in internet technologies. Technically, IMS utilises Session Initiation Protocol (SIP) for call communication. Potentially, SIP clients might reside in coexistence network family like IPv6 and/or IPv4. The coexistence of SIP clients considered a serious issue in SIP communication and IPv6 migration in general. In this paper a SIP-Proxy IP Translator (SPIPT) is proposed to translate SIP call between from IPv6 to IPv4 and vice versa. The proposed solution comes to insure successive connectivity in term of IP version compatibility. The experiment shows acceptable CPU usage, throughput, and Call Response Time parameters. SIP proxy hits negligible amount (1.93%) of CPU usage when 100 calls load. In addition, throughput also stays with the safety level with 1.9 Kbps in the same 100 calls. In sum, the solution aims to reduce call setup complexity and leverages user experience which in turn accelerates IPv6 transition.